Synthesis of thiohistidines and its metabolic pathway precursors - Khonde, Lutete Peguy (Department of Chemistry, 2017)
Natural thiohistidines such as ergothioneine and ovothiols are biosynthesized by actinomycetes, fungi and many parasitic protozoa, respectively. Actinomycetes such as Mycobacterium tuberculosis produce mycothiol and ergothioneine as their principal low molecular mass thiols. It is only very recently that the link between ergothioneine and tuberculosis disease has started to emerge, these studies suggested that ergothioneine is essential for the survival of Mycobacterium tuberculosis, the causal agent of tuberculosis. The biosynthesis of ergothioneine involved five enzymes encoded by the genes egtA, egtB, egtC, egtD and egtE. Because of the essentiality of these enzymes, in particular EgtD, could be considered as a potential tuberculosis drug target. Ergothioneine is a newly discovered vitamin and is widely used in cosmetics as an antioxidant, whereas ovothiol biosynthesis has received interest for the synthetic design of potential trypanosomal drugs. However, the commercial availability of these thiohistidines is limited, mainly due to multiple challenges associated to their synthesis or isolation from natural sources. This study describes the improved total synthesis of the super-antioxidant, ergothioneine and all its biosynthetic pathway intermediates, including deuterated versions thereof. A simple, short and high yielding novel process of the synthesis of ergothioneine was developed. Additionally, enzymatic methods were also considered for the desulfurisation step. The C-S lyase experiments mediated by Mycobacterium smegmatis cell-free lysate provided small scale transformations by the C-S lyase, EgtE, acting on its substrate, hercynylcysteine sulfoxide. Overoxidation of the latter substrate provided a sulfone that inhibited ergothioneine biosynthesis. While hercynylcysteine sulfoxide is known to be the substrate in Neurospora crassa, the EgtC enzyme in mycobacteria prefer γ-glutamyl hercynylcysteinesulfoxide as its precursor to ergothioneine. Hence, the need for sufficient quantity of this important metabolite has motivated the development of the first total synthesis of EgtC enzyme substrate, γ-glutamylhercynylcysteine sulfoxide. Finally, interesting synthetic challenges toward the synthesis of the most powerful natural related ovothiol, completes this study.